Medical Laboratory Director Competencies: State of the Basic Medical Sciences and Global Perspective - Mohammad Erfan Zare; Reza Meshkani; Mojtaba Abbasi; Farhad Shaveisi Zadeh; Atefeh Nasir Kansestani (Tehran University of Medical Sciences, 2017)
Background and Aim: There has been a long-lasting debate among medical laboratory-associated specialists about required competencies and educational background to qualify for directing medical laboratories in Iran. The aim of this study was to provide a comprehensive review regarding required training and competencies for becoming a medical laboratory director in Iran and all around the world. Materials and Methods: A thorough search of the literature was carried out in scientific databases including Web of Science, Science Direct, Springer Link, Wiley Online, PubMed, Scopus, SID and web-based search engines such as Google and Google Scholar. Results: The results revealed detailed required competencies for directing medical laboratories in the United States of America, Canada, European Federation of Clinical Chemistry and Laboratory Medicine (EFLM) and its many affiliated European countries. Conclusion: Our results indicate that in all assessed countries, specialists of basic medical sciences and also physicians, after passing certifying examinations, are equally qualified to direct medical laboratories. Indeed, Iran is the only country within the evaluated ones, in which basic medical sciences specialists (which have their own specific curriculum and are educated as clinical majors) have been eliminated from directing medical laboratory and the position has almost exclusively been available for graduates of pathology and it is important to revise this approach.